Untargeted metabolomics analysis of Physalis pubescens L. with respect to different varieties - Yan, Song; Li, Jialei; Chen, Kaixin; Shan, Shan; Zhang, Shan; Gao, Yang; Liu, Bin (Frontiers in Nutrition, 2025)
Physalis pubescens L. is a nutritious fruit with recognized pharmacological value, yet its comprehensive metabolomic profile remains unexplored. This study aimed to investigate the metabolomic differences among three distinct varieties of P. pubescens, with a focus on the influence of fruit size. An untargeted metabolomics approach employing UPLC-ESI-MS/MS was utilized. Multivariate statistical analyses, including PCA and PLS-DA, revealed a clear separation in metabolic profiles, primarily driven by fruit size. Comparative analysis between large-fruited variety B and small-fruited varieties S and T identified 67 significant differential metabolites. Notably, the flavonoid quercetin was not detected in large-fruited variety B under our analytical conditions, and the relative content of most phenylpropanoid metabolites was significantly lower in large-fruited variety compared to small-fruited varieties. Conversely, 17 metabolites, including certain amino acids and riboflavin, were up-regulated in large-fruited variety. Pathway analysis highlighted riboflavin metabolism as a key distinguishing pathway. Our findings demonstrate that fruit size may be a major factor influencing the phytochemical composition of P. pubescens. The novelty of this work lies in establishing fruit size as a major factor shaping the phytochemical composition of P. pubescens. These findings provide a metabolic foundation for selecting varieties with desired nutraceutical properties and for guiding future quality control and breeding programs.